PENGGUNAAN MODEL DISKRIMINAN ALTMAN Z-SCORE UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN PADA PERUSAHAAN MANUFAKTUR OTOMOTIF YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2015 – 2017 - Candra Ayuning Pawestri; Edi Wibowo; Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to find the results of Altman Z-Score discriminant model in predicting the potential for bankruptcy of the automotive manufacturing companies listed on the IDX period 2015 – 2017. The data use in this study are the company’s annual financial statements published by the IDX period 2015 – 2017. The sampling technique uses purposive sampling with a sample of 8 companies. The result showed that there were 5 companies in the bankrupt category during the study period namely PT. Indomobil Sukses International Tbk, PT. Multistrada Arah Sarana Tbk, PT. Nipress Tbk, PT. Prima alloy Steel Universal Tbk, dan PT. Intraco Penta Tbk, 1 company is in the grey area namely PT. Goodyear Indonesia Tbk in 2016 – 2017, while 1 company was in the healthy category for three consecutive years namely PT. Garuda Metalindo Tbk,and 1 company was in the bankrupt category in 2015 – 2016 then the company managed to make improvements both in management and in its financial structure, namely PT. Multi Prima Sejahtera Tbk which is in the healthy category in 2017.